Majority of Rural Residents Compost Food Waste: Policy and Waste Management Implications for Rural Regions - Niles, Meredith T. (Frontiers in Sustainable Food Systems, 2020)
A growing number of municipalities and states are implementing household food waste diversion efforts such as curbside compost programs, though these programs present challenges for participation and implementation. While many food waste diversion programs are occurring in densely populated regions, understanding food waste management in rural regions is less studied. This research examines the food waste perceptions and current and future food waste management behaviors of residents in Vermont, one of the most rural U.S. states, through a representative telephone survey of Vermont residents (n=583) in 2018. The findings suggest 55% of residents support banning food waste from landfills. Furthermore, 72% of residents compost at least some of their food waste currently and more than 75% anticipate doing so in the future. Conversely, 34% of residents anticipate using the garbage or a curbside compost pickup program in the future with urban county residents, renters, and those currently using garbage most interested in curbside programs. The majority of respondents were unwilling to pay anything additional for curbside compost pickup programs. These results suggest food waste management strategies in rural regions may be different than densely populated areas, particularly for programs that may require significant investments and have limited participation given the popularity of home composting. As a result, greater investment in education and infrastructure for backyard composting may be an important component of rural food waste management.